Types and Role of Social Capital in The Configuration Among Actors of Sendangbiru Coastal Community Business Contract - Anthon Efani; Asfi Manzilati; Yenny Kornitasari (Sekolah Pascasarjana Universitas Brawijaya, 2020)
The business activities of coastal communities do not only run based on business mechanisms, the business problems often are solved by social mechanisms. The aim of this research is to identify the types and role of social capital in the configuration among actors of coastal communities’ business contracts. This study uses a qualitative approach by phenomenology method to capture the actual phenomenon of business contracts relationship on coastal communities. The results show that the types of social capital can be seen from first, the trust: a lasting unwritten employment contract and debt that had never paid off. Second, the network: reflected in the closeness of the actors’ relationship which is influenced by the experience of cooperation, adherence to business contracts, and contractual ties to strengthen social relations. Third, the norm: the contract is applied to all business activities (business financing to fish marketing). In turn, social capital contributes to the running of business contracts due to the strong ties among fishermen and ship managers (pengambek) which can maintain the sustainability of fishing businesses, facilitate the information networks, minimize conflicts, and maintain brotherhood among actors.